Empirical Evidence on Satisfaction with Privatization in Latin America - Bonnet, Céline; Dubois, Pierre; Martimort, David; Straub, Stéphane (World Bank, 2013)
Since the 1980s, privatization of formerly state-owned firms has been extensively implemented by governments across Latin America. Despite the fact that most evaluations of the process fail to find significant adverse efficiency and welfare effects, there has been a strong surge in public discontent with such policy in the region. This paper performs a systematic empirical analysis of the determinants of such dissatisfaction, using survey data from Latinobarometro covering 17 countries over the period 1998-2008, complemented by country level data on macroeconomic, political, and institutional aspects as well as data on privatization. Dissatisfaction appears to respond to absolute and relative welfare effects, and we find a robust U-shaped effect in term of education and income levels, with individuals in the middle of such distributions being more critical with the outcome of privatizations.